ANEMIA DAN KEK PADA IBU HAMIL SEBAGAI FAKTOR RISIKO KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) (Studi di Wilayah Kerja Puskesmas Juwana Kabupaten Pati) - Susi Yunita Haryanti; Dina Rahayuning Pangestuti; Apoina Kartini (Jurnal Kesehatan Masyarakat (Undip), 2019)
Low Birth Weight Babies (LBW) is one of the major nutrition problems that have an impact on neonatal mortality. The infant mortality rate (IMR) in Pati is ranked second in Central Java (8,4%). LBW prevalence in Indonesia is ranked ninth in the world. The prevalence of LBW cases in Pati Regency in 2017 was 3.7%. This study aims to prove that anemia and KEK of pregnant women as a risk factors for LBW infants in the working area of Juwana Health Center Pati Regency. This study was an observational analytic research with a case control approach. Sampling technique with quota sampling. Subjects were 20 cases of mothers who delivered LBW babies while in the control group as many as 20 were mothers who delivered to NBW babies. Data on hemoglobin levels and size of the upper arm circumference were taken from the children's maternal health books (book of MCH). Data on energy sufficiency level, protein sufficiency level, and iron intake were obtained by the Food Frequency Questionnaire (FFQ). Data analysis by chi-square test. Anemia prevalence in the study was 45% while the prevalence of CED was 42.5%. Anemic women trimester II with an average Hb level of 10.7 ± 1.35 g/dL The use of iron intake was not higher (95%) than mothers who were not anemic (40%). Mothers CED with LiLA size ranges 23.7 ± 1.24 cm times have energy intake (95%) and protein (40%) is lacking. The research variables which risk factors of LBW were anemia in mothers (p = 0.001, OR = 9.333), CED in mothers (p = 0.004, OR = 7.429). Exposure to cigarette smoke was a confounding variable that associated with the incidence of LBW (p = 0.027). Attention to the nutritional status of women of childbearing age and pregnant women so that it can be known as early as possible the risk factors for KEK and anemia to prevent LBW cases.